For the polynomial function 2x^4 - x^3 + 2x^2 - 4x - 3, evaluate the following h(3)

h(x) = 2x^4 - x^3 + 2x^2 - 4x - 3, h(3);
h(3) = 2(3)^4 - (3)^3 + 2(3)^2 - 4(3) - 3;
h(3) = 2(81) - 27 + 2(9) - 12 - 3;
h(3) = 162 - 27 + 18 - 15;
h(3) = 162 - 9 - 15;
h(3) = 138

japs2310qa|Points 1979|

Question

Asked 3/13/2013 9:50:54 PM

Updated 7/18/2014 5:08:31 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [7/18/2014 5:08:30 AM], Confirmed by andrewpallarca [7/18/2014 5:08:31 AM]

Rating

There are no new answers.

27,098,144

questions answered

There are no comments.